1995
DOI: 10.1002/app.1995.070551011
|View full text |Cite
|
Sign up to set email alerts
|

Frictional properties of polyolefins treated with fluoroelastomer processing aids

Abstract: SYNOPSISA friction measurement system was designed that made possible the measurement of the friction coefficient between a polymer melt and a metal die wall. The shear stresses developed in the capillary rheometer and the friction coefficient measured in the friction measurement system were compared in a n attempt to understand the mechanism of fluoroelastomer processing aids (FPA) in the extrusions of polypropylene (PP) and linear low-density polyethylene (LLDPE). The apparent viscosity drops of LLDPE treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Table 1 provides the means and ranges for the values of k for the nonwoven mats at the different PP and normal stress levels. The values in Table 1 includes the data for the different temperature levels and dwell [12] and Gang et al [20] for solid PP. The frictional response of the mats with no PP fibers was substantially lower than the values in the literature [7][8][9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 provides the means and ranges for the values of k for the nonwoven mats at the different PP and normal stress levels. The values in Table 1 includes the data for the different temperature levels and dwell [12] and Gang et al [20] for solid PP. The frictional response of the mats with no PP fibers was substantially lower than the values in the literature [7][8][9].…”
Section: Resultsmentioning
confidence: 99%
“…Gang et al[20] found k for PP to drop to 0.017-0.021 at a higher temperature of 210 C. For solid wood, k was found to be between 0.10 and 0.13 at Representative frictional load curve for nonwoven mats at a surface temperature of 180 C, a 7.6-MPa normal load, and a 0-s dwell time.…”
mentioning
confidence: 99%
“…This literature has had a rebirth in the late 1980s and 1990s [26 to 28] for linear low-density polyethylenes. The precipitation of fluoropolymers on die surfaces and its ability to induce slip in polyethylene [11,12,14,15,29] over a very wide range of conditions has also been noted. Reports of slippage with polymers other than polyethylene are scarce.…”
Section: Occurrence Of Slippagementioning
confidence: 97%
“…We have already mentioned the work of Turner and Moore 8 with stearic acid in rubber compounds. The precipitation of fluoropolymers on die surfaces and its ability to induce slip in PE over a very wide range of conditions has been described by various authors [23][24][25][26][27] in recent years. Reports of slippage with polymers other than PE are scarce.…”
Section: Occurrence Of Slippagementioning
confidence: 99%